2015
DOI: 10.1038/nclimate2569
|View full text |Cite
|
Sign up to set email alerts
|

Effects of long-term variability on projections of twenty-first century dynamic sea level

Abstract: Sea-level rise 1 is one of the most pressing aspects of anthropogenic global warming with far-reaching consequences for coastal societies. However, sea-level rise did 2-7 and will strongly vary from coast to coast 8-10 . Here we investigate the long-term internal variability e ects on centennial projections of dynamic sea level (DSL), the local departure from the globally averaged sea level. A large ensemble of global warming integrations has been conducted with a climate model, where each realization was forc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0
1

Year Published

2015
2015
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 34 publications
(18 reference statements)
0
29
0
1
Order By: Relevance
“…It is substantial at interannual to multidecadal time scales ( Fig. S4; see also Lyu et al 2016;Bordbar et al 2015) and it masks part of the forced signal during the twentieth century (Carson et al 2015;Richter and Marzeion 2014;Lyu et al 2014;Jordà 2014). Here the unforced variability explains a significant part of the spread among climate models' twentieth-century dynamic sea level change patterns (cf.…”
Section: A Contribution From Dynamic Sea Levelmentioning
confidence: 92%
“…It is substantial at interannual to multidecadal time scales ( Fig. S4; see also Lyu et al 2016;Bordbar et al 2015) and it masks part of the forced signal during the twentieth century (Carson et al 2015;Richter and Marzeion 2014;Lyu et al 2014;Jordà 2014). Here the unforced variability explains a significant part of the spread among climate models' twentieth-century dynamic sea level change patterns (cf.…”
Section: A Contribution From Dynamic Sea Levelmentioning
confidence: 92%
“…While the internal climate variability has a relatively small effect on GMTSL, it can be larger regionally (Hu and Deser 2013), mainly on shorter (up to multidecadal) time scales, but also on centennial time scales (Carson et al 2015;Bordbar et al 2015;Monselesan et al 2015). We have compared DSL trends for the five different forcing experiments over various periods and find that, while the overall response to the external forcings is consistent, the patterns show more variability over shorter (decadal to multidecadal) periods because of the larger influence of internal climate variability.…”
Section: Regional Patterns In Dynamic Sea Level Change a Ensemble Mementioning
confidence: 99%
“…Hu and Deser [161] showed that even by the middle of this century, unforced variability leads to an uncertainty of up to a factor of two in coastal projections, the largest spread (in proportional terms) being on the north Pacific and north Atlantic coasts, despite the very small spread in projections of global mean thermal expansion. Bordbar et al [162] found that even after 100 years, the spread in local projections due to unforced variability may be comparable to global thermal expansion.…”
Section: Regional Projections and Emergence Time Of The Forced Signalmentioning
confidence: 99%
“…Several recent studies have evaluated the time of emergence of sea level change, with various definitions, in the CMIP5 dataset. For ocean dynamical sea level change (which excludes GMSLR), the local signal is not detectable in the majority of the ocean even after 100 years of anthropogenic forcing [162,164] (Figs. 4 and 5).…”
Section: Regional Projections and Emergence Time Of The Forced Signalmentioning
confidence: 99%